2012
DOI: 10.1021/ar300161g
|View full text |Cite
|
Sign up to set email alerts
|

Laser Trapping Chemistry: From Polymer Assembly to Amino Acid Crystallization

Abstract: Laser trapping has served as a useful tool in physics and biology, but, before our work, chemists had not paid much attention to this technique because molecules are too small to be trapped in solution at room temperature. In late 1980s, we demonstrated laser trapping of micrometer-sized particles, developed various methodologies for their manipulation, ablation, and patterning in solution, and elucidated their dynamics and mechanism. In the 1990s, we started laser trapping studies on polymers, micelles, dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
184
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 136 publications
(189 citation statements)
references
References 56 publications
5
184
0
Order By: Relevance
“…28 High-temperature accelerates reactions and thus leads to supersaturated regions formed in the beam center. 31 Violent convection induced by the gradient field transports the supersaturated solution into lower-temperature areas, leading to a burst of nucleation and the formation of nanostructures, in accordance with the Wilson−Frenkel growth theory. 28 In view of the above, we adopted a near-infrared CW laser to irradiate a precursor solution (with a specially added dye) for the synthesis of ultrathin CdS HNWs.…”
Section: ■ Introductionsupporting
confidence: 61%
“…28 High-temperature accelerates reactions and thus leads to supersaturated regions formed in the beam center. 31 Violent convection induced by the gradient field transports the supersaturated solution into lower-temperature areas, leading to a burst of nucleation and the formation of nanostructures, in accordance with the Wilson−Frenkel growth theory. 28 In view of the above, we adopted a near-infrared CW laser to irradiate a precursor solution (with a specially added dye) for the synthesis of ultrathin CdS HNWs.…”
Section: ■ Introductionsupporting
confidence: 61%
“…All these phenomena are schematically shown in Fig. 1 [14]. In parallel with the studies on crystallization and crystal growth, we are exploring new trapping dynamics of nanoparticles by femtosecond laser pulses and have found a unique behavior for polystyrene nanoparticles by the pulse [15].…”
Section: Introductionmentioning
confidence: 97%
“…Optical tweezers, which uses a tightly-focused laser beam to exert radiation force at a focal point [17], have been used for trapping and manipulating of microparticles such as living cells and polymer microspheres in bioscience [18]. This technique can also trap smaller nanoparticles such as polymer chains in aqueous solution [19]. Ishikawa et al first reported optical trapping of PNIPAM in an aqueous solution [20].…”
Section: Introductionmentioning
confidence: 99%